2022
DOI: 10.1155/2022/3490055
|View full text |Cite|
|
Sign up to set email alerts
|

Multiagent Culture Algorithm-Based Interactive Design of College English Online Teaching Process

Abstract: Traditional educational techniques and conceptions no longer match the need of the society for talent training. It is due to the fact that educational reforms are deepening and more open interactive teaching models have begun to be gradually implemented in college English instruction. The method’s innovation and reform can not only fully respect the students’ dominating position but also entice students to devote themselves to the English classroom with greater zeal which is helpful in allowing for deeper know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…First, the employment situation of Developer College students is outlined, as well as the shortcomings of job assistance courses. Peng [25] investigated the interactive teaching mode's application strategies in college classrooms to maximise the efficacy of class time and encourage high-quality development among today's modern college students.…”
Section: Literature Surveymentioning
confidence: 99%
“…First, the employment situation of Developer College students is outlined, as well as the shortcomings of job assistance courses. Peng [25] investigated the interactive teaching mode's application strategies in college classrooms to maximise the efficacy of class time and encourage high-quality development among today's modern college students.…”
Section: Literature Surveymentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%